The Effectiveness of Management Incentives in UK Based Private Equity Owned Companies - Gill, Michael (2020)
I analyse the effects of Sweet Equity and Salary on the performance of Private Equity (PE) owned firms between 2010 and 2020. My sample focuses on a peer group of similar industrially focused companies localised to the United Kingdom. My research documents that PE specific incentives, like sweet equity, and more general remuneration elicit significant positive effects on firm performance in PE owned companies. However, I find little evidence to suggest that private equity owned companies outperform a similar public peer group during the time period. My results raise the question as to whether Sweet Equity and other equity-based incentives produce their desired outcome, or whether other factors play a more significant role.